Establishment of an Optimal Portfolio with The Markowitz Model and Single Index Model - Nisa' , Nurina Khoirun; Listyani , Tyas; Winarni, Winarni; Suroto, Suroto (Serat Acitya, 2024)
This study aims to find out how much expected return and optimal portfolio risk and the best model between the Markowitz model and the single index model in forming optimal portfolios in banking sub-sector companies for the 2018-2022 period. This type of research includes applied quantitative descriptive. The research data uses secondary data in the form of stock closing prices, JCI and monthly BIC interest rates. The survey population is 29 companies. Data analysis uses the Markowitz model and single index model. The results showed that the stocks that make up the optimal portfolio with the Markowitz model are 12 company stocks that provide an expected return of 1.41%, an absolute risk of 4.48%, and a relative risk of 318.96%. While the single index model consists of 10 company stocks that provide an expected return of 4.65%, an absolute risk of 10.21%, and a relative risk of 219.68%. The research results are expected to contribute to investors, that the single index model is better than the Markowitz model.